Lecture réflexive ou érudite ? Quelques considérations sur le choix de méthode d’enseignement de la littérature en philologie romane contemporaine - Kędzia-Klebeko, Beata (2023)
“The subjective […] surrounds the objective” This statement by G. Lanson (Lanson 1919: 113) seems to fit in perfectly with the line of argument of the present analysis, while remaining a valid indication for the university literature teacher in contemporary neo-philological studies. It should be noted that students often start learning French when they enter university. What is the place of literature studies, then? The choice is not obvious for teachers faced with the reserve of non-readers of literature, on the one hand, and the demands of academic excellence, on the other. In a socio-cultural context aimed primarily at the currently recognised horizontal dimension of knowledge, the question arises as to whether and to what extent it is possible to adopt a scientific reading perspective, such as that sought by neo-philological studies. It seems that the search for the personal engagement among FLE students, leading them to discover the similar experiences to their own that the fictional world presents, can be seen as a first step towards the appreciation of literary foreign language studies.
Keywords: academic reading in FLE; subject-reader (sujet-lecteur); reflexivity; experience; erudition